2009
DOI: 10.1270/jsbbs.59.269
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in dry matter production and physiological nitrogen use efficiency in rice (<i>Oryza sativa</i> L.) varieties

Abstract: The objective of this study was to investigate varietal differences in dry matter production and physiological nitrogen use efficiency (PNUE) using a wide range of rice (Oryza sative L.) varieties at an early growth stage. The results provide useful information for breeding suitable varieties for cultivation under conditions of low soil fertility or with reduced fertilizer use for sustainable agriculture. Thirty-one rice varieties were used, and seedlings were grown under 8 nitrogen treatment conditions. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 29 publications
(32 reference statements)
1
36
1
Order By: Relevance
“…2), suggesting that N uptake capacity and its utilization efficiency of indica I differ from those of indica II groups. produced inconsistent results regarding the association of PNUE with biomass production. For example, in a study where a variation in PNUE ((dry weight of N treatmentdry weight of non-N control)/(N content of N treatment-N content of non-N control)) among 31 cultivars was examined under varying N conditions, a significant cultivar difference in PNUE was found (Namai et al, 2009), although the definition of PNUE was different from our study. They suggested that the variation reflects the genetic and/or cultural backgrounds of the cultivars employed, including 20 indica and japonica types.…”
Section: Genotypic Variation In N Uptake Ability and Its Use Efficiencycontrasting
confidence: 75%
“…2), suggesting that N uptake capacity and its utilization efficiency of indica I differ from those of indica II groups. produced inconsistent results regarding the association of PNUE with biomass production. For example, in a study where a variation in PNUE ((dry weight of N treatmentdry weight of non-N control)/(N content of N treatment-N content of non-N control)) among 31 cultivars was examined under varying N conditions, a significant cultivar difference in PNUE was found (Namai et al, 2009), although the definition of PNUE was different from our study. They suggested that the variation reflects the genetic and/or cultural backgrounds of the cultivars employed, including 20 indica and japonica types.…”
Section: Genotypic Variation In N Uptake Ability and Its Use Efficiencycontrasting
confidence: 75%
“…Since A/G ratios represent the relative abundance of Asp-derived and Gluderived FAAs in the grains, the difference observed between the two grain types appears to indicate key differences in the manner in which the two rice ecotypes accumulate these free amino acids in their respective endosperms. Rice researchers have identified many fundamental differences between indica and japonica-type rices (Wang et al 1998, N'tanos and Koutroubas 2002, Lon et al 2004, Namai et al 2009). The difference observed in the present study might therefore fit within the broader framework of the indica-japonica dichotomy.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed a large genotypic difference in NUE among cultivars of O. sativa, and the indica cultivar, Kasalath, showed the highest N sensitivity (Namai et al, 2009). Duan et al (2007) also confirmed that, when NO 3 -were applied together with NH 4 + , cultivars with high NUE showed higher N accumulation, dry matter production, and yield than those with low NUE and suggested that there was a close relationship between NO 3 -application and NUE.…”
mentioning
confidence: 54%
“…Currently, there are many reports on the physiological difference between the subspecies of O. sativa. Namai et al (2009) reported that the indica type has higher N sensitivity in the dry matter productivity than the japonica type. In addition, the indica type develops roots more extensively than the japonica type under the LN condition (Namai et al, 2009).…”
Section: Dry Matter Production and Nue Under Different N Conditionsmentioning
confidence: 99%
See 1 more Smart Citation